(3GdGJaGb GdadSWjfi GdGSQGFjdi ZRI GQjMG (B: s (3OQGSI bGfhfjI ai VhA bhGYO GdbGfhf GdOhdi GdYGe (B/ s - (3NjQi jhSa eQjcHs; (3UdGM GdOjf YGeQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3JfGhdfG ai gPg GdOQGSI GJaGbGJ GdSdGe GdJi GHQeJ Hjf efXeI GdJMQjQ GdadSWjfjI h GSQGFjd hGdJi GQJHWJ HGdYOjO ef GdehVhYGJ GdTGFcI ai GdbGfhf GdOhdi (B: (3hGdJi GJVM dfG HMb GfgG JTcd hGMOI ef Gge h GOb GdehVhYGJ GdbGfhfjI GdJi JSJMb GdOQGSI hbO MGhdfG LgO GdWGbI (B: (3Gf fJYQV HTiA ef GdJaUjd dcd GdLRFjGJ GdeQJHWI HehVhY GdOQGSI MJi jecf Gf fbOe QDjI eJcGedI Yf GdGJaGbGJ hYf GdbVjI GdadSWjfjI heQGMd JWhQgG (B: (3hGdGSS hGdVhGHW GdbGfhfjI dJShjJgG JShjI YGOdI hOGFeIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2006s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B587-617s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GdGJaGb GdadSWjfi GdGSQGFjdis; (3ZRI GQjMGs; (3efXeI GdJMQjQ GdadSWjfjIs; (3GdYdGbI GdadSWjfjI GdESQGFjdjI s; (3GdGYJQGas; (3GdWHjYI GdbGfhfjI ddGYJQGa s; (3GdGYJQGa GdOhdj HMQcGJ GdJMQjQ GdhWfj s; (3GYJQGa efXeI GdJMQjQ GdadSWjfjI HESQGFjd s; (3GdGYJQGa GdOhdj HefXeI GdJMQjQ GdadSWjfjI s; (3GdMce GdPGJj GdadSWjfj s; (3Mb JbQjQ GdeUjQ s; (3GdMce GdPGJj s; (3GJaGbjGJ ChSdh s; (3eYGgOI ajjfG s; (3GdJShjI GdSdejI s; (3bVjI GdbOS s; (3bVjI GddGLFjf s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs